Technology as a factor in the cultural development of mankind: a study of the production nature of primitive culture - Sovhyra, Tetiana (National Academy of Managerial Staff of Culture and Arts Herald, 2021)
Purpose of article. Explore technological progress in the context of the development of a primitive culture. The methodology is based on an integrated approach and relies on analytical (when analyzing philosophical, art history, cultural studies literature on the subject of research), historical (when clarifying the stages of development of primitive culture), and conceptual (when analyzing the role of technology in the cultural development of mankind) research methods. The scientific novelty of the article lies in the fact that for the first time the formative role of technology in the cultural development of mankind is investigated, and also the cooperative nature of the production of artifacts of primitive culture is determined. Conclusions. As a result of the study of archaeological finds of primitive culture, it has been established that in the course of cultural evolution, tools of labor have become cultural artifacts, works of art. The emergence of production technologies (stone processing, fire control, metal melting) radically transformed the specifics of the organization of production activities, and therefore changed the course of cultural development. Therefore, in the course of the study, the formative role of technology in the formation of artistic culture was proved.